Uma breve história da Teologia da Libertação: Um olhar crítico sobre os primeiros 20 anos - Renato Westphal, Euler (Vox Scripturae - Revista Teológica Internacional, 2011)
The Theology of Liberation has appeared as reaction to the political, social, and culture framework. That grew up in Latin America. The most part of population in Latin America is poor. According to Theology of Liberation, the Christian faith needs to promove endeavour of superation from the opression. The preferential option for the poor is resulting from the obedience to the gospel. Moreover, the theology searches the efficacy, that expresses through the liberation of the poor people from all their social and politics opression. The Theology of liberation is a legitim search to obedience to the gospel in the history. However, it is necessary to say, that the Theology of liberation didn´t give atention to the radicality of the sin. Thereby, the salvation of the people is limited to the social transformation. Thus the poor person is loading in his person the Christ of God, because Jesus was poor.